The Modeling of Funicular Structure Stability of Cordoba Mosque in Spain - Sedayu, Agung (Proceeding International Conference on Science and Engineering, 2019)
The Cordoba Mosque Spain is proof of the glory of Islam in the field of architecture and building construction. This mosque is supported by thousands of funicular that support reliable structural stability and construction. The arrangement of natural stone that complements the arch with a simple system that can make this mosque survive until now. This research is to find out the funicular structure of the Spanish Cordoba Mosque. The method is a structural modeling assisted by SAP 2000 non linear structure analysis program. The results showed that the weight of the stone that formed the curve made it work in place. Beside that, the level of stone curvature durability has supported the durability of the building structure material. Configuration and funicular dimensions also support the rigidity against horizontal, vertical and moment loads. Funiculars with each other connect and encourage building effects produce prestress in the all mosque building.